2022
DOI: 10.1101/2022.08.12.22278203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in risk factors and symptoms associated with SARS-CoV-2 and Rhinovirus test positivity in King County, Washington: A Test-Negative Design Study of the Greater Seattle Coronavirus Assessment Network

Abstract: Importance: Few US studies have reexamined risk factors for SARS-CoV-2 positivity in the context of widespread vaccination and new variants or considered risk factors for co-circulating endemic viruses, such as rhinovirus. Objective: To understand how risk factors and symptoms associated with SARS-CoV-2 test positivity changed over the course of the pandemic and to compare these to the factors associated with rhinovirus test positivity. Design: This test-negative design study used multivariable logistic regr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Given the smaller population size in South King County, one potential explanation for higher local spread in that region is reduced access to social and economic capital and health care resources needed to curb community transmission. Previous studies looking at SARS-CoV-2 test positivity in King County at a census tract level have found that a higher test positivity was associated with various socioeconomic indicators including lower educational attainment, higher rates of poverty, and high transportation costs [16,17]. Additionally, they found that communities with a higher proportion of people of color, which are more likely to be located in South King County, were also associated with higher test positivity in 2020.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Given the smaller population size in South King County, one potential explanation for higher local spread in that region is reduced access to social and economic capital and health care resources needed to curb community transmission. Previous studies looking at SARS-CoV-2 test positivity in King County at a census tract level have found that a higher test positivity was associated with various socioeconomic indicators including lower educational attainment, higher rates of poverty, and high transportation costs [16,17]. Additionally, they found that communities with a higher proportion of people of color, which are more likely to be located in South King County, were also associated with higher test positivity in 2020.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, they found that communities with a higher proportion of people of color, which are more likely to be located in South King County, were also associated with higher test positivity in 2020. Hansen et al [17], specifically found that having a place of residence in South King County was associated with SARS-CoV-2 test positivity. The stark contrast in health outcomes between North and South King County has been previously attributed to historical redlining and systemic racism, whereby decades of racial segregation prevented communities of color from residing in northern areas of Seattle and were forced into the south into present day South King County [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Given the smaller population size in South King County, one potential explanation for higher local spread in that region is reduced access to social and economic capital and health care resources needed to curb community transmission. Previous studies looking at SARS-CoV-2 test positivity in King County at a census tract level have found that a higher test positivity was associated with various socioeconomic indicators including lower educational attainment, higher rates of poverty, and high transportation costs (15,16). Additionally, they found that communities with a higher proportion of people of color, which are more likely to be located in South King County, were also associated with higher test positivity in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they found that communities with a higher proportion of people of color, which are more likely to be located in South King County, were also associated with higher test positivity in 2020. Hansen et al (34), specifically found that having a place of residence in South King County was associated with SARS-CoV-2 test positivity. The associations between test positivity and socioeconomic status are not a unique King County phenomenon; they have been found in various metropolitan areas around the US (30,31,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation